2010
DOI: 10.3390/molecules15010315
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II)/Cationic 2,2’-Bipyridyl System as a Highly Efficient and Reusable Catalyst for the Mizoroki-Heck Reaction in Water

Abstract: A water-soluble and air-stable Pd(NH3)2Cl2/cationic 2,2’-bipyridyl system was found to be a highly-efficient and reusable catalyst for the coupling of aryl iodides and alkenes in neat water using Bu3N as a base. The reaction was conducted at 140 °C in a sealed tube in air with a catalyst loading as low as 0.0001 mol % for the coupling of activated aryl iodides with butyl and ethyl acrylates, providing the corresponding products in good to excellent yields with very high turnover numbers. In the case of styrene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 66 publications
(57 reference statements)
1
24
0
Order By: Relevance
“…With respect to aryl bromides, we found that only strongly-activated aryl bromides could be utilized for the mono Mizoroki-Heck reaction in the presence of tetrabutylammonium bromide [50]. Unfortunately, double Mizoroki-Heck coupling failed when these aryl bromides were used [25,33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to aryl bromides, we found that only strongly-activated aryl bromides could be utilized for the mono Mizoroki-Heck reaction in the presence of tetrabutylammonium bromide [50]. Unfortunately, double Mizoroki-Heck coupling failed when these aryl bromides were used [25,33].…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported that the PdCl2(NH3)2/cationic 2,2′-bipyridyl catalytic system can very efficiently catalyze monoarylation of activated olefins using water as a solvent [50]. Based on these results, we slightly modified the reaction conditions in order to study the double Mizoroki-Heck reaction using the same catalytic system.…”
Section: Introductionmentioning
confidence: 99%
“…We have extensively studied this reaction in organic solvents and more recently in aqueous solution, [6] since water emerges as a sustainable solvent and has several advantages such as low cost, abundance, easy separation from organic products [7,8]. However, the exclusive use of water often leads to modest yields and the use of phase transfer agent additives like tetraalkylammonium salts are essential in order to circumvent such limitation [9,10]. Recently, the effect of cyclodextrins as phase-transfer agent on the C-C cross-coupling reaction in water was demonstrated [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Mizoroki-Heck reaction generally implies the use of palladium complexes with phosphine-containing ligands. Huang et al [4] recently showed that palladium complexes with 2,2′-bipyridine ligands are very efficient catalysts in Mizoroki-Heck reaction [4]. Taking into account that these reactions require basic medium, anionic palladium complex is desirable or an acid residue should be present in one ring of the ligand.…”
mentioning
confidence: 98%